1984
DOI: 10.1111/j.1532-950x.1984.tb00765.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Aspects of the Healing of Excisional Wounds on the Leg and Body of Horses

Abstract: Standardized 20 mm diameter excisional skin wounds were made on the body and distal limbs of 6 ponies at 18,12,4, and 2 weeks prior to biopsy. The results of comparative area analysis of leg and body wounds show that leg wounds take significantly longer to heal than body wounds. There is a longer preparatory phase and a greater amount of wound retraction in the leg wounds. At 12 weeks postwounding, the area of the epithelium covering the wound site is significantly larger in the leg wounds compared to the flan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
0
8

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 4 publications
5
60
0
8
Order By: Relevance
“…The average contraction rate of the wounds at 21 DPO were significantly different between the metacarpal and lumbar regions; the lumbar region presenting a higher contraction rate in this period in both groups (Figure 2). The difference in the speed of healing between lumbar and metacarpal wounds in this study was expected, as it has been shown that lumbar wounds undergo a faster healing process, with a higher centripetal contraction, thinner granulation tissue, and a faster formation of crusts compared with metacarpal wounds (JACOBS et al, 1984;WHITE, 1995). According to JACOBS et al (1984) andWILMINK et al (1999), the delay in wound healing in distal regions of the limbs when compared with the trunk in the equine species, is due to a long healing phase, characterized by large retraction of the wound, low rates of epithelialization and early termination of wound contraction.…”
Section: Lucas Et Almentioning
confidence: 70%
See 1 more Smart Citation
“…The average contraction rate of the wounds at 21 DPO were significantly different between the metacarpal and lumbar regions; the lumbar region presenting a higher contraction rate in this period in both groups (Figure 2). The difference in the speed of healing between lumbar and metacarpal wounds in this study was expected, as it has been shown that lumbar wounds undergo a faster healing process, with a higher centripetal contraction, thinner granulation tissue, and a faster formation of crusts compared with metacarpal wounds (JACOBS et al, 1984;WHITE, 1995). According to JACOBS et al (1984) andWILMINK et al (1999), the delay in wound healing in distal regions of the limbs when compared with the trunk in the equine species, is due to a long healing phase, characterized by large retraction of the wound, low rates of epithelialization and early termination of wound contraction.…”
Section: Lucas Et Almentioning
confidence: 70%
“…The difference in the speed of healing between lumbar and metacarpal wounds in this study was expected, as it has been shown that lumbar wounds undergo a faster healing process, with a higher centripetal contraction, thinner granulation tissue, and a faster formation of crusts compared with metacarpal wounds (JACOBS et al, 1984;WHITE, 1995). According to JACOBS et al (1984) andWILMINK et al (1999), the delay in wound healing in distal regions of the limbs when compared with the trunk in the equine species, is due to a long healing phase, characterized by large retraction of the wound, low rates of epithelialization and early termination of wound contraction. BERRY & SULLINS (2003) state that lower blood supply, oxygen tension and temperature in addition to the presence of insufficient quantities of cytokines, determine the different patterns of healing between the different anatomical regions of the horse.…”
Section: Lucas Et Almentioning
confidence: 70%
“…In such cases epithelization, must be relied upon to cover the remaining granulation bed (Swaim 1980;Jacobs et al, 1984). Finally, using minimum concentration of chitosan (0.1%), with shortest time (42-50-day), in the current study relative to other studies for complete healing in donkey's wound, give hopeful idea in handling of wound dressing in another species of animal particularly equine one.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, wound contraction started at 14 th day PW and proceeded rapidly during the following 4-5 weeks. The extent and the rate of wound contraction during this phase (the rapid healing phase) of wound healing depends upon the degree of myofibroblasts organization and the contraction of its actin contents (Jacobs et al, 1984& Wilmink et al, 1999b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation